Half square : half crazy - Mangion, Eric; Pécoil, Vincent; Reynaud, Lili; Wetterwald, Elisabeth (Zürich : JRP-Ringier Kunstverlag AG Zürich Kunsthalle Zürich Kunstverein Hamburg, 2007)
Achour, Boris ; Afif, Saadane ; Armleder, John ; Boyce, Martin ; Coindet, Delphine ; Creed, Martin ; Curlet, François ; Dafflon, Stéphane ; Decrauzat, Philippe ; Floyer, Ceal ; Friedman, Tom ; Gander, Ryan ; Gastaldon, Vidya ; Gony, Marjolaine ; Guyton, Wade ; Hein, Jeppe ; Hempel, Lothar ; Könitz, Alice ; Lambie, Jim ; Manaranche, Carole ; Mayor, Genêt ; Mazières, Damien ; Mercier, Mathieu ; Monk, Jonathan ; Mosset, Olivier ; Nicolai, Olaf ; Panchal, Gyan ; Parrino, Steven ; Peinado, Bruno ; Pettibon, Raymond ; Pernet, Hugo ; Perret, Mai-Thu ; Pinaud, Pascal ; Piper, Owen ; Raguénès, Loïc ; Rothschild, Eva ; Schäfer, Gitte ; Schüwer-Boss, Hugo ; Scott, Michael ; Strunz, Katja ; Szarek, Vincent ; Tatham, Joanne ; O'Sullivan, Tom ; Thurman, Blair ; Tremblay, John ; van Golden, Daan ; Walsh, Dan ; Wermers, Nicole ; White, Pae ; Wolter, Lars
biog., ind. tent. p. 163-173
Engels
Exhibition. Half square, half crazy. Nice. Villa Arson Nice. 2007-02-10. 2007-06-03
boek